Approaches to Implementation of Motivation as the Complex Conditions of Increase of Efficiency of Social and Labor Relations: International Experience - Kobersy, Iskandar S.; Khasiyeva, Leyla G.; Yakhina, Viktoria D.; Ignatyeva, Olga V.; Goloshchapova, Ludmila V.; Shkurkin, Dmitry V.; Sadykova, Liana R. (International Review of Management and Marketing, 2016)
The relevance of studies motivating work mainly compounded by the extensive way of formation and development of the Russian economy that emerged in the last decade low innovation activity of employees and organizations in general, "deficit" highly skilled and motivated workers, especially blue-collar occupations. In addition, over the past 20 years there have been many changes in people's minds: to change the structure of motives of labor behavior of workers and staff of the organization system of values, the composition of prestigious professions and, finally, change the value of labor in society. In modern conditions for national competitiveness, sustainable development of the country as a whole and individual organizations and companies need to use powerful and effective resource - human capital. Intellectualization of the modern Russian production sets new requirements for the workforce, which in turn requires the development of science Labor Economics. Management issues are extremely complex motivation, as labor behavior is the external manifestation of internal interests, motivations, attitudes and values of the person. For their resolution requires a systematic approach, a comprehensive study of man at work. Keywords: innovation activity, efficiency, control of personnel JEL Classifications: D2, G1, J08